2011
DOI: 10.1073/pnas.1105734108
|View full text |Cite
|
Sign up to set email alerts
|

Fast-folding α-helices as reversible strain absorbers in the muscle protein myomesin

Abstract: The highly oriented filamentous protein network of muscle constantly experiences significant mechanical load during muscle operation. The dimeric protein myomesin has been identified as an important M-band component supporting the mechanical integrity of the entire sarcomere. Recent structural studies have revealed a long α-helical linker between the C-terminal immunoglobulin (Ig) domains My12 and My13 of myomesin. In this paper, we have used single-molecule force spectroscopy in combination with molecular dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
84
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 56 publications
7
84
0
Order By: Relevance
“…Proteins are biological nanomachines that utilise mechanical forces in a wide range of cellular processes [1][2][3][4] . These important processes range from the translocation of proteins/DNA across membranes 5,6 , the degradation of proteins by molecular 30 chaperone proteins 7 , the mechanical resilience of proteins within a molecular scaffold [8][9][10][11] and the conversion of mechanical signals into electrochemical signals 12, 13 ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins are biological nanomachines that utilise mechanical forces in a wide range of cellular processes [1][2][3][4] . These important processes range from the translocation of proteins/DNA across membranes 5,6 , the degradation of proteins by molecular 30 chaperone proteins 7 , the mechanical resilience of proteins within a molecular scaffold [8][9][10][11] and the conversion of mechanical signals into electrochemical signals 12, 13 ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This non-monotonic behavior is reminiscent of the "catch-bond" phenomenon observed in some inter-molecular structures in which intermediate loads induce unfolding more slowly than either low or high loads. [16][17][18][19][20][21][22][23][24][25][26] The MFPT calculated at 10 pN was longer than that calculated at both 0 pN and 100 pN. Pathway calculations indicated that this non-monotonic behavior appeared to be related to the formation of non-native (i.e., non α-helical) structures, namely π helices, more prominently at this intermediate load level.…”
Section: Introductionmentioning
confidence: 94%
“…Load magnitudes tested included 0, 5,10,15,20,25,30,40,70, and 100 pN. The load direction, fixed throughout the simulations, was set in the [0 0 1] direction corresponding to the helix's nominal axis as defined by the vector between the center of mass of the load end groups.…”
Section: A Computational Protocolmentioning
confidence: 99%
See 2 more Smart Citations